2015
DOI: 10.1111/cts.12325
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Comorbidities and Interest in Research Participation Among Clients of a Nonprofit Food Distribution Site

Abstract: Background Persons accessing food from nonprofit distribution sites face numerous challenges and typically have significant unmet health needs. However, given limited and intermittent healthcare system engagement, this vulnerable population is under-represented in clinical research. We sought to better understand the health needs of a non-clinical population to inform future research and interventions. Methods Focus groups were conducted in English (n=4) and Spanish (n=4) with clients of Crossroads Community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…This was somewhat surprising, as prior research has shown that those with chronic conditions are more likely to participate 6, 40, 41, 42. Another unexpected finding was that those who have insurance were less likely to have had the opportunity to participate, and those who were uninsured reported greater opportunity.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This was somewhat surprising, as prior research has shown that those with chronic conditions are more likely to participate 6, 40, 41, 42. Another unexpected finding was that those who have insurance were less likely to have had the opportunity to participate, and those who were uninsured reported greater opportunity.…”
Section: Discussionmentioning
confidence: 85%
“…This was somewhat surprising, as prior research has shown that those with chronic conditions are more likely to participate. 6,[40][41][42] Another unexpected finding was that those who have insurance were less likely to have had the opportunity to participate, and those who were uninsured reported greater opportunity. Furthermore, those who reported not being able to afford to go to the doctor, and those without a job reported greater willingness to participate.…”
Section: Wwwcts-journalcommentioning
confidence: 99%
“…We measured health correlates in 3 broad areas associated with food security and food assistance: general health and functional status, health risk behaviors, and health care access indicators ( 2 , 4 , 5 , 9 , 17 21 ). Health characteristics — except body mass index (BMI, kg/m 2 ), which was measured directly — were self-reported.…”
Section: Methodsmentioning
confidence: 99%
“…Most previous studies on the health of food insecure populations recruited participants from a single food assistance program (eg, a WIC office, a food pantry) ( 9 12 ). This practice limits our knowledge as to whether health status varies among people participating in public and private programs.…”
Section: Introductionmentioning
confidence: 99%
“…Elsewhere we described how clients of the same center reported multiple health challenges and comorbidities, including among others, high blood pressure, diabetes, arthritis, and mental health conditions such as depression, schizophrenia, and anxiety (Higashi et al. ). In the present analysis, we show how household health, economic instability, and food insecurity are inextricably linked across family and social networks, creating cumulative and interdependent challenges faced by multiple household members.…”
Section: Introductionmentioning
confidence: 99%